Representing suicide: Giving voice to a desire to die?. (January 2022) - Marsh, Ian; Winter, Rachel; Marzano, Lisa
Drawing on interview and online ethnographic data from a study of suicide on the railways, this paper describes the ways in which many of the concepts, assumptions and practices of mainstream suicide prevention are challenged in the accounts of those who are planning, or have enacted, a suicide attempt. We reflect on the ethical dilemmas which can arise for researchers (and practitioners) when lived experience accounts diverge – theoretically, morally and in terms of practical implications – from present-day expert ones. In online, 'pro-choice' suicide discussions, people describe beliefs, attitudes, ways of thinking and acting which stand in contrast to existing professional and clinical descriptions of suicide and suicidal behaviour. Most obviously, there is often a rejection of 'pro-life' positions, which are framed as ideological, oppressive and naïve. For researchers engaging in online ethnography of 'pro-choice' spaces, dilemmas can arise in relation to the representation of perspectives which fundamentally challenge not only prevailing norms within suicide research and prevention practice but socio-cultural norms more widely. Similar issues can arise when considering how best to represent research participants when their accounts diverge from accepted 'expert' knowledge and beliefs. In-depth qualitative interviews with those who have thought about or attempted to take their own life indicate that existing theories and models of suicide which start from assumptions of deficit and pathology underestimate the extent to which suicide, as the end result of an often-complex series of actions, requires a person to engage in logistical processes of planning, decision-making, imagination and adaptation. The accounts described here, gathered using two different methodological approaches, highlight the ethical issues which can surface when there are competing claims to (expert) knowledge, as well as differences in beliefs, attitudes and moral stance towards life and death. We argue that researchers need to reflect on their own ethical-moral position in relation to suicide, and on the practical consequences of their privileging of some voices at the expense of other, less well represented, ones.